Trends of child sexual abuse in Indonesia: From research design to data analysis - Mardliyah, Sjafiatul; Roesminingsih, Erny; Nugroho, Rivo; Widyaswari, Monica; Afandi, Agus; Santoso, Thomas (Edelweiss Applied Science and Technology, 2025)
Child sexual abuse (CSA) remains a significant concern globally, including in the Indonesian context. This research furnishes a thorough examination of CSA research trajectories through the application of content analysis. Scholarly articles were sourced from the Scopus database, spanning 2009 to 2024, with particular emphasis on CSA within Indonesia. The originality of this investigation resides in its methodical assessment of the trends, research methodologies, subjects, and approaches employed in CSA studies, thereby offering a holistic viewpoint of the prevailing body of literature. This research addresses the following inquiries: (1) What trends characterize the volume of CSA research in Indonesia? (2) What variations are evident in the employed research methodologies? (3) Which thematic areas are predominantly addressed in CSA research? (4) What data collection strategies are implemented? (5) Which research subjects receive the most attention? (6) What analytical methods are utilized? Employing the principles of content analysis, data was amassed in October 2024. The findings revealed a notable escalation in CSA research after the COVID-19 pandemic, predominantly centering on quantitative approaches. Most studies employed document analysis as their focal point while prioritizing non-victim perspectives. Concurrently, the legal aspect of CSA emerged as the most frequently investigated theme. Systematic methodologies predominated both data collection and analysis techniques. The results underscore several principal recommendations: (1) Foster an increase in qualitative research to yield a deeper understanding of the intricate dimensions of CSA. (2) Emphasize victim-centered research to enhance the contextual comprehension of traumatic experiences. (3) Incorporate the Gender Equality and Social Inclusion (GESI) framework into CSA research to cultivate a more inclusive outlook. (4) Ensure alignment between methodology and research design to ascertain robust findings.